The Impact of the Effectiveness of Smart Quality Management on the Profitability Enterprises of Major Asian Companies - Kareem, Jasim Mohammed (South Asian Journal of Social Sciences and Humanities, 2024)
This study aims to identify the extent of the influence of smart quality management practices  and their impact on the profitability performance of major Asian companies. This paper used  a sample of 143 major companies for the purpose of testing the relationship from the years  2020 to 2023. The study concluded that there is a positive and important link among smart  quality management and profitability performance. Smart quality management is considered  important in modern concepts that represent a new technical method for managing business  processes and institutions in general. Smart quality management aims to improve profitability  and productivity. This study considers smart quality management to be an integrated  management system that aims to improve the firm’s reputation and growing its profits and  market share, and then confirm its existence and link in the field of effort.
Keywords: Smart quality management; profitability performance; major Asian companies